Baltic States: the most suitable country to open a cryptocurrency exchange - Šerstobitovs, Antons (Riga Graduate School of Law, 2019)
This thesis conducts research on the laws of the Baltic countries, on the territory of which it is possible to open a service for the presentation of services related to virtual currencies, such as the cryptocurrency exchange and the cryptocurrency wallet. The goal is to establish the most "friendly" law that would assist the entrepreneur in opening a new legitimate and regulated enterprise in this field of activity. The study is primarily aimed at studying the practical application of skills related to the ability to use the knowledge gained in the study of law. The schemes described in the study are working and based not only on the legal basis but also on the study of individual enterprises operating in the field under discussion. The information given from the first to the fifth chapters of the thesis should help the reader to learn what virtual currency, cryptocurrency exchange, cryptocurrency wallet, and the technologies used in their interaction systems are. Further chapters are mainly focused on the study of the legal regimes of both the European Union and the Baltic countries (Latvia, Estonia and Lithuania), in some way affecting the scope of actions that may be carried out in conducting business. Subsequently, a comparison is made of these legal regimes, as a result of which it was revealed that the most “friendly” and progressive in the matter of the legal regime regarding this business is Estonia. From a practical point of view, it was revealed that the legal aspect is not so important for starting a business in this environment, and everything depends not only on it but also on the wishes and views on this issue of the entrepreneur himself
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Cryptocurrencies